De novo variant in GUCY2D gene causing atypical cone-rod dystrophy in a consanguineous family and literature review - Xin-He Fang; Fa-Yong Ke; Wen-Qing Zou; De-Jun Zhu; Mei-Jiao Ma; Yuan-Yuan Lian; Xue-Li Wu; Rui-Hua Wei; Xun-Lun Sheng (International Journal of Ophthalmology)
AIM: To analyze the pathogenicity and clinical features of patients in a consanguineous cone-rod dystrophy (CRD) family due to heterozygous variants in the GUCY2D gene. METHODS: Whole exome sequencing was used to screen for pathogenic genes and candidate pathogenic variants were obtained by bioinformatics analysis. Sanger sequencing was used for validation and familial co-segregation analysis to determine pathogenic variants. Pymol software was applied to produce a 3D structure image of the protein to analyze the structural and functional alterations of the protein. The pathogenicity of genetic variants was evaluated according to ACMG guidelines. RESULTS: The chief clinical symptoms of this proband included obvious visual impairment, protanopia and deuteranopia, peripheral punctate pigment, arteriolar attenuation, structural and functional abnormalities revealed by optical coherence tomography (OCT) and electroretinography (ERG) including thinning of the outer retinal layer, a discontinuous external limiting membrane (ELM) and ellipsoid zone (EZ), granular hyperreflective projections between the retinal pigment epithelium and the interdigitation zone, severe attenuation of photopic responses with mild reduced scotopic responses. Whole-exome sequencing revealed that the proband carried a heterozygous variant of the GUCY2D gene: c.2512C>T: p.Arg838Cys. Three-dimensional molecular structure analysis of the protein revealed that amino acid 838 was mutated from polar positively charged arginine to polar uncharged cysteine, and the spatial structure of the protein changed greatly. Sanger sequencing co-segregation analysis confirmed that such a variant was detected in neither the phenotypically normal parents nor the daughter of the proband, which was presumed to be a de novo one. The variant was determined to be pathogenic according to ACMG guidelines. The heterozygous variant at the same site was detected in the abnormal proband's son with moderate attenuation of photopic electroretinographic responses and normal scotopic electroretinographic responses, supporting autosomal dominant inheritance. CONCLUSION: The de novo variant causing atypical autosomal dominant CRD is identified in a Chinese consanguineous family and this variant passes through this family in an autosomal dominant mode of inheritance, revealing the complex diversity and unpredictability of the inheritance mode for common single-gene genetic disease.